2020
DOI: 10.1016/j.heliyon.2020.e05612
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of clinical practice guidelines for the management of paediatric dental emergencies applicable to the COVID-19 pandemic, using the AGREE II instrument. A systematic review

Abstract: Objective To assess the quality of Clinical Practice Guidelines (CPG) related to the management of paediatric dental emergencies applicable to the COVID-19 pandemic, through the use of the measuring instrument AGREE II (Appraisal of Guidelines for Research and Evaluation in Europe). Sources and Data collection A rigurous online search of CPG was accomplished among the main CPG compilers: National Institute for Health and Care Excellence (NICE), National Guideline Cleari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
11
0
5
Order By: Relevance
“…The low score for the remaining domains, was also reported for other guidelines carried out in the context of the COVID-19 pandemic. 46 , 47 Norris et al 48 who evaluated WHO guidelines generated during four previous emergencies related to recent infectious diseases (H1N1, H7N9 virus, MERS-CoV, and Ebola), concluded that few guidelines met international standards for reliable and evidence-based CPGs. Moreover, they pointed out CPGs´ weaknesses, such as limited mention of systematic reviews, failure to perform external peer reviews, and incomplete information with regard to development methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The low score for the remaining domains, was also reported for other guidelines carried out in the context of the COVID-19 pandemic. 46 , 47 Norris et al 48 who evaluated WHO guidelines generated during four previous emergencies related to recent infectious diseases (H1N1, H7N9 virus, MERS-CoV, and Ebola), concluded that few guidelines met international standards for reliable and evidence-based CPGs. Moreover, they pointed out CPGs´ weaknesses, such as limited mention of systematic reviews, failure to perform external peer reviews, and incomplete information with regard to development methods.…”
Section: Discussionmentioning
confidence: 99%
“…In our research, only two guidelines 27 , 28 presented a score higher than 60% in at least three domains. Notwithstanding the above, whether performed during or outside a pandemic context, 46 , 47 , 49 the quality of the CPGs in the dental field in general tend to be of substandard quality with AGREE II overall rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…É importante que o desenvolvimento de diretriz siga um rigor na metodologia para que seja aplicada em diversos serviços, especialmente na área da saúde, com a declaração de quaisquer tipos de influência e/ou conflitos entre as organizações financiadoras e o conteúdo do documento 39 . Ressalta-se que raramente as instituições financeiras fazem declaração explícita de que seus interesses não influenciaram as recomendações, entretanto, são cruciais para uma boa avaliação [40][41] .…”
Section: Discussionunclassified
“…A baixa pontuação do domínio D5 se deve à falta de descrição das potencialidades, riscos, benefícios e estratégias na implementação das recomendações, as quais, na maioria, se referem ao uso farmacológico no tratamento da Covid-19, em que ainda persistem dúvidas e que necessitam de maior investigação 40 .…”
Section: Discussionunclassified